2021
DOI: 10.3390/cancers13133292
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Risk Factors Associated with Class 1A Uveal Melanoma Patients

Abstract: In uveal melanoma (UM), gene expression profiling (GEP) is commonly used to classify metastatic risk into three groups (Class 1A, 1B, and 2). Class 1A patients have a lower metastatic risk of 2% at 5 years compared to other groups. We aimed to describe clinical features associated with the development of metastasis in this low-risk group. This single-center IRB-approved retrospective case series review included all UM patients between February 2006 and March 2019 with an archived or fresh specimen classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…In contradiction to these predictions, our study showed a higher actuarial rate of metastasis in the GEP 1A subgroup than in the GEP 1B subgroup and a very low rate of metastasis in the GEP 1B cases. The metastatic rate we observed in our GEP 1A patients is similar to the rate reported by Ballhausen and coworkers in their GEP 1A patients [6].…”
Section: Discussion/conclusionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contradiction to these predictions, our study showed a higher actuarial rate of metastasis in the GEP 1A subgroup than in the GEP 1B subgroup and a very low rate of metastasis in the GEP 1B cases. The metastatic rate we observed in our GEP 1A patients is similar to the rate reported by Ballhausen and coworkers in their GEP 1A patients [6].…”
Section: Discussion/conclusionsupporting
confidence: 92%
“…More recently, a separate group evaluated and reported the actuarial rate of metastasis in 73 patients with a GEP 1A UM in a single-center retrospective study [6]. The median follow-up time in this group was 37 months.…”
Section: Introductionmentioning
confidence: 99%
“…Cook and Alsina cite a report by Demirci and coworkers [5] (which we acknowledged and cited in our recent publication) that supports the expected separation of survival curves of GEP class 1A versus1B patients. These authors reported a similar number of cases as we did.…”
supporting
confidence: 58%
“…Similarly, a 5-year metastatic rate of 17% was observed in a study of metastatic risk factors restricted to patients with class 1A tumors [21].…”
Section: Discussionmentioning
confidence: 65%